2008
DOI: 10.1021/ed085p288
|View full text |Cite
|
Sign up to set email alerts
|

Peer Mentoring in the General Chemistry and Organic Chemistry Laboratories. The Pinacol Rearrangement: An Exercise in NMR and IR Spectroscopy for General Chemistry and Organic Chemistry Laboratories

Abstract: Collaborative work in the laboratory is valued at Wofford College (1-3), as it is at many other institutions. Earlier collaborations at Wofford have allowed students in our physical chemistry classes to share data and to work with students from other institutions on computational chemistry projects. We now wish to report on preliminary efforts in establishing a program involving laboratory collaboration of another sort-between students enrolled in organic chemistry and those studying general chemistry.Organic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 16 publications
(22 reference statements)
0
5
0
Order By: Relevance
“…Students are guided toward discovering the relationship between bond strength, bond order, and vibrational frequency through a series of exercises that include observing masses oscillating on springs, modeling bond stretching computationally, and obtaining IR spectra of several related compounds. Although several previously published general chemistry experiments use IR spectroscopy as an educational component, only a few examine bond properties. Of these, one is somewhat similar to the laboratory described herein in that IR spectra are obtained and Hooke’s law is demonstrated via masses and springs . However, this experiment extends the learning as students build and conduct molecular modeling experiments on their own molecules in a computational chemistry program, animate the molecular vibrations of their compounds, and generate a theoretical IR spectrum for them.…”
mentioning
confidence: 95%
“…Students are guided toward discovering the relationship between bond strength, bond order, and vibrational frequency through a series of exercises that include observing masses oscillating on springs, modeling bond stretching computationally, and obtaining IR spectra of several related compounds. Although several previously published general chemistry experiments use IR spectroscopy as an educational component, only a few examine bond properties. Of these, one is somewhat similar to the laboratory described herein in that IR spectra are obtained and Hooke’s law is demonstrated via masses and springs . However, this experiment extends the learning as students build and conduct molecular modeling experiments on their own molecules in a computational chemistry program, animate the molecular vibrations of their compounds, and generate a theoretical IR spectrum for them.…”
mentioning
confidence: 95%
“…Another successful model involves organic chemistry students mentoring general chemistry students on using molecular spectroscopy to identify an unknown organic compound they had synthesized. It was reported that this was one of the general chemistry students’ favorite laboratories; further the authors felt that the experience motivated the general chemistry students to continue their studies in chemistry . It was similarly reported that seventh grade students’ interest and level of participation increased after using newly developed technology-based modules and receiving instruction from college mentors, connecting the seventh grade girls with women who shared similar backgrounds and chose to study science in college .…”
Section: Introductionmentioning
confidence: 96%
“…It was reported that this was one of the general chemistry students' favorite laboratories; further the authors felt that the experience motivated the general chemistry students to continue their studies in chemistry. 8 It was similarly reported that seventh grade students' interest and level of participation increased after using newly developed technology-based modules and receiving instruction from college mentors, connecting the seventh grade girls with women who shared similar backgrounds and chose to study science in college. 9 In another mentoring program, high school and middle school students benefited from enriching exposure to polymers and material sciences and, additionally, because they "may not have the opportunity to interact with college students; the exposure to college mentors...may inspire them to pursue college degrees in science and engineering."…”
Section: ■ Introductionmentioning
confidence: 98%
“…Over the past 15 years or so, there have been several NMR based experiments/activities suitable for the first year chemistry experience described in the literature. Some focus on the analysis of student prepared samples, some relate NMR data to electronegativity, periodic trends, or pH, , some are multi-week, multi-instrument spectroscopy experiences which involve the use of spectra from known compounds, , and some focus on the identification of unknowns following some pre-lab component (handout or tutorial) where students are introduced to spectral identification prior to the actual laboratory activity. We believe we have developed a unique cooperative learning hands-on laboratory experience relating information acquired from the 13 C NMR experiment to molecular structure without the use of known compounds, or without prior student knowledge of NMR details and methods of spectroscopic interpretation.…”
Section: Introductionmentioning
confidence: 99%